The p53 response: a new mitochondrial role for cofactor strap - Maniam, S (2013)
Strap is a DNA damage responsive p53 cofactor, reflecting its control by the DNA damage signalling pathway. This study identified Strap at the mitochondria where it is damage regulated and can augment p53-dependent cytochrome c release leading to apoptosis. Moreover, p53 and Strap facilitate each other’s localisation from the mitochondria to the nucleus during the DNA damage response. Two ATM/ATR phosphorylation consensus sites in Strap were identified by mass spectrometry and phosphorylation of all the ATM/ATR consensus sites resulted in mitochondrial localisation of Strap during DNA damage. Targeting Strap to the mitochondria depletes cellular ATP when cells favour energy production through oxidative phosphorylation and sensitises cells to p53-dependent damage-induced apoptosis. These results thus imply that Strap co-ordinates different arms of the p53 response, and might be responsible for integrating its mitochondrial and nuclear functions.